Navigating Barriers: Teachers’ Perspectives on Implementing TBLT to Develop EFL Speaking Skills - Wahyuni, Emi Nurul; Setyarini, Sri; Purnawarman, Pupung (Universitas Jambi, Magister Program of English Education Department, 2026)
Task-Based Language Teaching (TBLT) has become a widely advocated approach to developing English speaking competence in EFL classrooms due to its interactive and communicative nature. Nevertheless, its implementation in practice is often influenced by various factors that may undermine its effectiveness. This study aims to explore the challenges faced by the teachers while implementing TBLT to teach speaking and the solutions they employ to deal with these challenges. To achieve this objective, a qualitative approach was used, involving 11 English teachers from secondary schools who were purposely selected based on their experience in employing TBLT in their classrooms. Using a thematic analysis of qualitative data collected from open-ended questionnaires, the study categorizes findings into two major themes: the obstacles encountered in practical application and the possible solutions suggested. The findings show that several challenges occurred during its implementation, such as a rigid curriculum, classroom management issues in large classes, and student reluctance due to insecurities or unfamiliarity with TBLT. To overcome these challenges, some suggestions were proposed by the teachers as the participants, including simplifying tass, integrating technology and authentic materials, and providing teacher training. This study offers practical insiieshts for educators and institutions aiming to integrate TBLT effectively into FL classroom practices.